PENGARUH KEPERCAYAAN, KEMUDAHAN PENGGUNAAN DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA E-COMMERCE SHOPEE DI BANDAR LAMPUNG - Tarisa Aulia (Journal Strategy of Management and Accounting Through Research and Technology (SMART), 2023)
The purpose of this study was to determine and test the effect of trust, ease of use and price on purchasing decisions at e-commerce Shopee in Bandar Lampung. This study uses a quantitative approach. The population of this study are consumers who have made purchases at e-commerce shopee in Bandar Lampung. The number of samples used in this study amounted to 140 respondents, with a total of 30 statement items from 3 variables. The data source used in this study uses primary data obtained by distributing questionnaires through the Google form. The data analysis technique in this study used multiple linear regression analysis using SPSS version 26. The results of this study indicate that trustworthiness, ease of use and price have a positive and significant effect on purchasing decisions at e-commerce shopee in Bandar Lampung.